Tolerance strategy of Chlorella sorokiniana to combined antibiotic stress revealed by transcriptomic analysis - Bowen Lian; Shaohang Li; Xinping Zheng; Zhonghao Fan; Haining Cao; Yongzheng Peng; Bo Wang; Min Wang; Hualong Wang (Environmental Pollution, 2026)

Aridity-dependent biodiversity and multi-trophic associations drive soil multifunctionality in dryland ecosystems - Jianyu Wang; Haining Zhang; Chunping Zhang; Bangjie Tang; Yuyu Li; Qinglan Hu; Zhangxing Zhang; Xinwen Li; Ran Xu; Miaochun Fan; Wenqing Chen (CATENA, 2026)

Orally engineered V-type starch nanohelices for orchestrated polyphenol delivery restore the gut-metabolism axis in obesity - Shiyu Fan; Chi Zhang; Pengpeng Sun; Haining Shi; Ying Tian; Aiqian Ye; Jian He; Yutong Wu; Qiaozhi Zhang; Linglin Fu (Chemical Engineering Journal, 2026)

Investigation of the Alterations in the Gut Microbiota and Intestinal Mucosa in Mice Infected with Echinococcus multilocularis - Deping Cao; Wenjun Huang; Mingquan Pang; Jiajing Li; Haitao Huang; Hui Ma; Dayu Li; Yufei Qin; Xiaohong Peng; Haining Fan (Acta Parasitologica, 2025)

Engineered flower-shaped MXene-copper nanowire composite facilitate mechanically tuned and sensitive field-effect transistors in miniaturized portable devices toward noninvasive NSCLC prognostic monitoring - Chengling Zhao; Bing Xia; Zhao Jin; Zhenkai Fan; Qiao Ge; Haining Hong; Haiwei Sang; Lixiang Li; Ansheng Wang (Chemical Engineering Journal, 2025)

Optimized Deployment of Generalized OCDM in Deep-Sea Shadow-Zone Underwater Acoustic Channels - Haodong Yu; Cheng Chi; Yongxing Fan; Zhanqing Pu; Wei Wang; Li Yin; Yu Li; Haining Huang (Journal of Marine Science and Engineering, 2025)
Communication in deep-sea shadow zones remains a significant challenge due to high propagation losses, complex multipath effects, long transmission delays, and strong environmental influences. In recent years, orthogonal chirp division multiplexing (OCDM) has demonstrated promising performance in underwater acoustic communication due to its robustness against multipath interference. However, its high peak-to-average power ratio (PAPR) limits its reliability and efficiency in deep-sea shadow-zone environments. This study applies a recently proposed generalized orthogonal chirp division multiplexing (GOCDM) modulation scheme to deep-sea shadow-zone communication. GOCDM follows the same principles as orthogonal signal division multiplexing (OSDM) while offering the advantage of a reduced PAPR. By segmenting the data signal into multiple vector blocks, GOCDM enables flexible resource allocation, optimizing the PAPR without compromising performance. Theoretical analysis and practical simulations confirm that GOCDM preserves the full frequency diversity benefits of traditional OCDM, while mitigating PARR-related limitations. Additionally, deep-sea experiments were carried out to evaluate the practical performance of GOCDM in shadow-zone environments. The experimental results demonstrate that GOCDM achieves superior performance under low signal-to-noise ratio (SNR) conditions, where the system attains a 0 bit error rate (BER) at 4.2 dB and 6.8 dB, making it a promising solution for enhancing underwater acoustic communication in challenging deep-sea environments.

A decade-long perspective on marine health changes in Dalian, China - Xiaocheng Wang; Yumeng Wang; Haining Wang; Jiangpeng Fan; Mian Li; Wentong Hao (Frontiers in Marine Science, 2025)
The ocean, serving as the cradle of life on Earth and the regulator of global climate, constitutes an invaluable resource repository for human survival and development. The preservation of ocean health is pivotal for the sustainable progression of human society. This study chose Dalian in China to assess the marine health using the Ocean Health Index (OHI) at the city-level by selecting appropriate parameters and reference points to align with data sources. The results indicated that the overall OHI score declined by 5.81 in Dalian from 2012 to 2022. For decades, the scores for Clean Waters and Coastal livelihoods and economies had consistently maintained perfection. The scores for Food Provision, Natural Products, and Carbon Storage increased, while those for Tourism and Recreation, Coastal Protection, Sense of Place, Artisanal Fishing Opportunities, and Biodiversity experienced decline. Food Provision saw the most substantial growth, increasing by 16.44, while Tourism and Recreation experienced the steepest decline, dropping by 30.57. It was indicated that the quality of seawater had consistently remained at a high level, and the economy developed well. However, there was a slight decline in marine health, with a notable downturn in tourism. Coastal ecosystems still face ongoing risks of degradation. For the next steps, the focus should be on coastal zone protection and revitalizing the tourism industry. Greater support and effective management should be provided to traditional fisheries. We recommend that parameters and reference points be standardized, and emphasize the importance of prioritizing the use of official data for calculations and assessments when applying the OHI at the city-level to ensure comparability.

Experimental and numerical investigation on near-field temperature and surface CO2 concentrations of buried dense phase CO2 pipeline leakage - Junpeng Zhang; Shaodong Jing; Zhenning Fan; Haining Liang; Junhui Zhang; Yan Zhang; Chunlong Sun; Jian Zhang (International Journal of Greenhouse Gas Control, 2025)

Bisphenol A removal with nitrification and denitrification: Occurrence, mechanism, and microbial mutualism - Xuekang Cao; Chao Liu; Xuemeng Zhang; Haining Huang; Xinyun Fan; Chuang Chen; Xu Duan; Yinguang Chen (Critical Reviews in Environmental Science and Technology, 2025)

Development of a throttling venting model for CO2 pipelines and study of venting characteristics - Yifan He; Shuai Yu; Xingqing Yan; Jiaran An; Zhenning Fan; Haining Liang; Jianliang Yu (Process Safety and Environmental Protection, 2025)

Rational construction of 2D/2D Ti3C2/BiOBr S-scheme heterojunction for the boosted photo-degradation of 4-dodecylmorpholine under visible light irradiation - Yuqin Cai; Yuelin Wei; Jiaxin Chen; Shuhong Lv; Deguang Wu; Yunfang Huang; Xuefeng Yu; Haining Liu; Leqing Fan; Jihuai Wu (Journal of Environmental Chemical Engineering, 2025)

Diffusion of Surface CO2 in Coalfield Fire Areas by Surface Temperature and Wind - Junpeng Zhang; Haiyan Wang; Cheng Fan; Zhenning Fan; Haining Liang; Jian Zhang (Natural Resources Research, 2025)

Evolutionary Analysis of Hypoderma Pantholopsum in Tibetan Antelopes on the Qinghai–Tibetan Plateau - Fan Zhang; Haining Zhang; Zhi Li; Ru Meng; Peiling Ye; Yong Fu (Acta Parasitologica, 2025)

Butylparaben induces glycolipid metabolic disorders in mice via disruption of gut microbiota and FXR signaling - Haining Du; Lili Cui; Xinyi Zhao; Ziteng Yu; Tianyue He; Boya Zhang; Xingpei Fan; Meimei Zhao; Ruijiao Zhu; Ziyi Zhang; Mengcong Li; Jiaxin Li; et al. (Journal of Hazardous Materials, 2024)

Preparation of housefly (Musca domestica) larvae protein hydrolysates: Influence of dual-sweeping-frequency ultrasound-assisted enzymatic hydrolysis on yield, antioxidative activity, functional and structural attributes - Fan Yang; Wen Chen; Mokhtar Dabbour; Benjamin Kumah Mintah; Haining Xu; Jiayin Pan; Chunhua Dai; Haile Ma; Ronghai He (Food Chemistry, 2024)

Polystyrene nanoplastics induce glycolipid metabolism disorder via NF-κB and MAPK signaling pathway in mice - Xingpei Fan; Xiaoyan Li; Jiaxin Li; Yuxia Zhang; Xiangjuan Wei; Hailong Hu; Boya Zhang; Haining Du; Meimei Zhao; Ruijiao Zhu; Daqian Yang; Yuri Oh; et al. (Journal of Environmental Sciences, 2024)

Synergistic effects of pH shift and heat treatment on solubility, physicochemical and structural properties, and lysinoalanine formation in silkworm pupa protein isolates - Haining Xu; Jiayin Pan; Mokhtar Dabbour; Benjamin Kumah Mintah; Wen Chen; Fan Yang; Zhaoli Zhang; Yu Cheng; Chunhua Dai; Ronghai He; Haile Ma (Food Research International, 2023)

Lambda-cyhalothrin induces lipid accumulation in mouse liver is associated with AMPK inactivation - Daqian Yang; Xiaotong Sun; Xiangjuan Wei; Boya Zhang; Xingpei Fan; Haining Du; Ruijiao Zhu; Yuri Oh; Ning Gu (Food and Chemical Toxicology, 2023)

High-fat diet and palmitate inhibits FNDC5 expression via AMPK-Zfp57 pathway in mouse muscle cells - Qian Guo; Boya Zhang; Haining Du; Ruijiao Zhu; Xiaotong Sun; Xingpei Fan; Xiangjuan Wei; DaQian Yang; Yuri Oh; Lei Fan; Changlin Wang; Ning Gu (Chemico-Biological Interactions, 2023)

Effects of Irrigation and Polymer-Coated Urea on Water-Nitrogen Productivity and Yield of Winter Wheat - Zhen Fan; Youxin Zhao; Haining Chen; Yurong Chen; Derui Bu; Jiyao Xu; Xinran Guo; Yue Wang; Xiaofei Tian (Journal of Soil Science and Plant Nutrition, 2022)

Production and Evaluation of a Novel Multi-Epitope Bivalent Vaccine Against Echinococcus multilocaularis Metacestode - Runle Li; Mingyuan Xin; Kunmei Liu; Bingwen Hu; Jingwei Ma; Pei Zhou; Lin Feng; Mingquan Pang; Ri-li Ge; Haining Fan; Le Guo; Feng Tang (International Journal of Peptide Research and Therapeutics, 2022)

Association of a novel antisense lncRNA TP73-AS1 polymorphisms and expression with colorectal cancer susceptibility and prognosis - Jiayao Fan; Huiqing Xu; Bing Liu; Fangyuan Jing; Qingfang He; Shasha Zheng; Haining Shi; Lefei Jiao; Chunhong Fan (Genes & Genomics, 2022)

Evaluation of Allicin Against Alveolar Echinococcosis In Vitro and in a Mouse Model - Chuanchuan Liu; Haining Fan; Lu Guan; Lan Ma; Ri-li Ge (Acta Parasitologica, 2022)
Purpose At present, the chemotherapy for alveolar echinococcosis (AE) is mainly based on albendazole (ABZ). However, more than 20% of patients fail chemotherapy. Therefore, new and more effective treatments are urgently needed. Allicin has been reported to have antibacterial and antiparasitic effects. The objectives of the present study were to investigate the in vivo and in vitro efficacy of allicin against Echinococcus multilocularis ( E. multilocularis ). Methods The effects of allicin on protoscolex survival and structural changes were evaluated in vitro . The 4-week-old BALB/c male mice used for in vivo modelling underwent inoculation of E. multilocularis protoscoleces by intraperitoneal injection, followed by intragastric administration of allicin for 6 weeks. Then, the effects of allicin on lymphocyte subsets, metacestode growth and host tissue matrix metalloproteinase 2 (MMP2)/MMP9 expression around metacestodes in mice were evaluated. The toxicity of allicin was further evaluated in vivo and in vitro . Results Att 40 μg/mL, allicin showed a killing effect on protoscoleces in vitro and treatment resulted in the destruction of protoscolex structure. Molecular docking showed that allicin could form hydrogen bonds with E. multilocularis cysteine enzymes. After 6 weeks of in vivo allicin treatment, the spleen index of mice was increased and the weight of metacestodes was reduced. Allicin increased the proportion of CD4 + T cells and decreased the proportion of CD8 + T cells in the peripheral blood and spleen. Pathological analysis of the metacestodes showed structural disruption of the germinal and laminated layers after allicin treatment. In addition, allicin inhibited the expression of MMP2 and MMP9 in metacestode-surrounding host tissues. At 160 μg/mL, allicin had no significant toxicity to normal hepatocytes but could inhibit hepatoma cell proliferation. At 30 mg/kg, allicin had no significant hepatorenal toxicity in vivo . Conclusion These results suggest that allicin exerts anti- E. multilocularis effects in vitro and in vivo and can enhance immune function in mice, with the potential to be developed as a lead compound against echinococcosis.

Evaluation of Drug Dissolution Rate in Co-amorphous and Co-crystal Binary Drug Delivery Systems by Thermodynamic and Kinetic Methods - Chunhui Hu; Fabin Zhang; Haining Fan (AAPS PharmSciTech, 2021)